2019
DOI: 10.1111/sjpe.12209
|View full text |Cite
|
Sign up to set email alerts
|

Management practices and SME performance

Abstract: We examine the association between management practices and SME performance in Britain over the period 2011–2015, using a unique dataset which links survey data on management practices with firm performance data from the UK's official business register. We find that SMEs are less likely to use formal management practices than larger firms. However, such practices appear to have demonstrable benefits for those SMEs who use them, being positively associated with firm survival, growth and productivity. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…Quantitative method of data analysis was used. It has the advantage of providing accurate results about a phenomenon or a set of activities and facilitates easy hypotheses testing by ensuring easy development of models and theories from empirical data (Forth and Bryson, 2019) Responses were collated, coded and summed up for each of the variables and for each of the participants. The relationships between the variables were measured using product moment correlation coefficient and the combined effect was measured using simple regression analysis.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative method of data analysis was used. It has the advantage of providing accurate results about a phenomenon or a set of activities and facilitates easy hypotheses testing by ensuring easy development of models and theories from empirical data (Forth and Bryson, 2019) Responses were collated, coded and summed up for each of the variables and for each of the participants. The relationships between the variables were measured using product moment correlation coefficient and the combined effect was measured using simple regression analysis.…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…Serrasqueiro et al (2018) identified some critical capabilities in the area of cost estimation, environmental scanning, assessment, and predictions, work definitions, clients' criteria as well as work objectives as the major variables of success. Others are; prompt product/service delivery Bocconcelli et al (2018) management knowledge and skills, business processes, evaluation of performance, business structure and systems (Ahmed et al, 2018;Wang and Zhou, 2019) business plan, (Arasa and K'Obonyo, 2012;Forth and Bryson, 2019;Ighodalo et al, 2019) managerial attitude and practices (Asikhia, 2010;Okwachi et al, 2013;Sabli and Latiff, 2019), strategy (Maney et al, 2014;Rizan, Balfas, and Purwohedi, 2019) and marketing (Omar and Anas, 2014;Van Scheers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the sample size, we used the following formula n = z 2 pqN e 2 (N − 1) + pqz 2 (1) where:…”
Section: Resultsmentioning
confidence: 99%
“…Entrepreneurs search for sustainable long-term business development by launching and leading high-growth firms in terms of job creation, wealth generation, and the development of effective entrepreneurial role models to maximize firm performance [2,3], especially when entrepreneurs increase their perceived behavioral control [4] and imitate reputed and successful entrepreneurs [5]. High-growth firms surge when they dispose of opportunity-based entrepreneurs, have large amounts of information, and are broad-market oriented [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the candidates to open the black box of the mechanism is wide. It extends from cross-national comparisons (Dastmalchian, 2020;Gilbert and Von Gilnow, 2015) and investigations based on company size (Arthur et al, 2019;Broszeit et al, 2019;Forth and Bryson, 2018;Wu et al, 2015) to studies where the mechanism has been brought closer to the shop floor level. Various dimensions of job quality, organisation culture and job satisfaction (Den Hartog and Vergurg, 2004;Garg, 2019;Lee et al, 2017;Wood and Ogbonnaya, 2018) -but also union density (Vazquez-Bustelo and Avella, 2019) and social capital (Jiang and Liu, 2015) -have been investigated as mediators between productivity and high-performance practices.…”
Section: Introductionmentioning
confidence: 97%